The Potential Role of Senescence As a Modulator of Platelets and Tumorigenesis - Valenzuela, Claudio A.; Quintanilla, Ricardo; Moore-Carrasco, Rodrigo; Brown, Nelson E. (Frontiers in Oncology, 2017)
In addition to thrombus formation, alterations in platelet function are frequently observed in cancer patients. Importantly, both thrombus and tumor formation are influenced by age, although the mechanisms through which physiological aging modulates these processes remain poorly understood. In this context, the potential effects of senescent cells on platelet function represent pathophysiological mechanisms that deserve further exploration. Cellular senescence has traditionally been viewed as a barrier to tumorigenesis. However, far from being passive bystanders, senescent cells are metabolically active and able to secrete a variety of soluble and insoluble factors. This feature, known as the SASP (Senescence-Associated Secretory Phenotype), may provide senescent cells with the capacity to modify the tissue environment and, paradoxically, promote proliferation and neoplastic transformation of neighboring cells. In fact, the SASP-dependent ability of senescent cells to enhance tumorigenesis has been confirmed in cellular systems involving epithelial cells and fibroblasts, leaving open the question as to whether similar interactions can be extended to other cellular contexts. In this review, we discuss the diverse functions of platelets in tumorigenesis, and suggest the possibility that senescent cells might also influence tumorigenesis through their ability to modulate the functional status of platelets through the SASP.